Determination of Random Periodic Structures in Transverse Magnetic Polarization (Communications in Mathematical Research, 2021)
Consider an inverse problem that aims to identify key statistical properties of the profile for the unknown random perfectly conducting gratingstructure by boundary measurements of the diffracted fields in transverse magnetic polarization. The method proposed in this paper is based on a novelcombination of the Monte Carlo technique, a continuation method and theKarhunen-Loève expansion for the uncertainty quantification of the randomstructure. Numerical results are presented to demonstrate the effectiveness ofthe proposed method.
Keywords: Random periodic structure; inverse scattering; Karhunen-Loève expansion; Monte Carlo-continuation-uncertainty quantification method.